Colonización y su influencia en la vulnerabilidad socioambiental de las comunidades nativas: Nuevo Perú y Nuevo Samaria, región Ucayali-2019 - Tirado Tirado, Elizabeth (2019)
The colonization of the Amazon by migrants from the mountains in search of new fertile and “free” lands to be exploited, stealthily increases. This phenomenon of migration and settlement of settlers is importantly transforming life in native communities. This transformation is especially very negative, generating a socioeconomic inequality between natives and immigrants. These new "colonizers" have turned natural ecosystems into agricultural areas through the use of unsustainable agricultural techniques such as the burning and rubbing of trees, this has caused some environmental impacts such as deforestation, soil degradation, decline of species of fish and game animals; All of these are the main causes of socioeconomic poverty in which native populations live by limiting access to and use of natural resources. Likewise, this process of interaction between settlers and natives implies changes and/or modifications in both cultures; being the most vulnerable, the native communities. Vulnerability is the condition presented by an individual, or group of people to be affected by some external factor. In this way, in the native communities of the Shipibo-Conibo ethnic group of the Iparía district: Nuevo Peru and Nuevo Samaria, belonging to the buffer zone of the El Sira Communal Reserve, they present these conditions due to their proximity and interaction with hamlets inhabited by settlers who came to extract timber, to make farms, for commerce, etc. significantly affecting the ecosystem services of your new place of residence and work. With this research work, it is intended to explain in a concrete way how the current colonization influences the socio-environmental vulnerability of the native communities of Nuevo Peru and Nuevo Samaria through their economic activities; mainly migratory agriculture that generates forest deforestation and soil degradation; as well as, it threatens the well-being of the native populations by the changes in their lifestyles.